The Effect of Honey and Zinc Cream as Topical Dressing for Epithelization in Diabetic Foot Ulcer - Muhammad Husaini; Asrizal Asrizal; Imam Budi Putra (Malahayati Nursing Journal, 2023)
ABSTRACT Diabetic foot ulcer is a complication that often serves Diabetes Mellitus patients. Currently, wound care has used dressings to keep the wound environment moist, but in general, foot wound care requires high costs, so it is necessary to figure out the alternative wound care that is really effective and cost-effective in wound healing. One type of alternative therapy for topical treatment of diabetic foot ulcers that can be used is topical honey. The aim of this research was to identify the effect of topical honey and zinc cream on epithelization in the treatment process for diabetic foot ulcers. This type of research is inquiries, namely intervention, and control group design. The sample consisted of 60 respondents consisting of 30 wound care groups using topical honey and 30 wound care respondents using zinc cream with the sampling technique, namely consecutive sampling. Honey was used with 87% honey concentration and lipid tissue epithelialization was measured using the Bates Jensen Wound Access Tool (BJWAT). Data analysis used the Mann-Whitney test as an alternative test for the independent t-test. The results showed that there was no significant difference in wound tissue epithelialization between the wound care group with zinc topical cream and honey topical cream (p-value 0.05). The Conclusions which is based on the results of analytical tests, wound care using topical zinc cream and topical wound care using honey did not have a significant difference in the epithelialization process of diabetic foot ulcers, but clinically the epithelialization process of diabetic foot wounds with topical honey treatment was faster than using zinc cream. It is recommended that topical wound care using honey can be used as an alternative topical in the treatment of diabetic foot ulcers. Keywords: Diabetic Foot, Honey, Ulcer, Zinc Cream